Mary Wilson - Ash, Jen (Sojourners for Justice Press, 2024)
"Mary Wilson was a 37-year-old Black woman who confessed to the killing of a white military officer at Fort Sam Houston, Texas, in 1913. While many of its details are still unknown, Mary Wilson's story sheds light on the ways Black women were and continue to be forced to navigate systems of state violence. In turn, those systems were/are deeply and historically interwoven with the legacy of slavery and the rise of the prison industrial complex in the United States after emancipation. The state and vigilantes repeatedly subject Black women to more violence when they defend themselves against interpersonal violence. Mary Wilson's case exemplifies these patterns of violence, but the authorities acquitted her, making her case unique. Mary went free based on a claim of self-defense."--Haymarket Books website